Printed Strain Sensors Using Graphene Nanosheets Prepared by Water‐Assisted Liquid Phase Exfoliation. Issue 9 (27th February 2019) - Manna, Kausik; Wang, Long; Loh, Kenneth J.; Chiang, Wei‐Hung
Abstract: A novel approach to leverage the extraordinary properties of graphene for designing thin film strain sensors is demonstrated. Graphene nanosheets (GNS) are produced from graphite by a liquid phase exfoliation (LPE) method using water along with N ‐methylpyrrolidinone (NMP) as cosolvents. It is found that the water‐NMP solvent system enhances the exfoliation yield and the stability of the GNS dispersion, thereby lowering the number of defects in the GNS basal plane. Both LPE‐based GNS and reduced graphene oxide (RGO) are synthesized for fabricating thin film strain sensors and for comparison purposes. Detailed micro‐Raman, X‐ray photoelectron spectroscopy, and transmission electron microscopy studies indicate that the as‐produced GNS exhibits lower defects than RGO nanosheets. The strain sensing study reveals that strain sensors fabricated using low‐defect GNS exhibit enhanced electrical and electromechanical properties, including higher electrical conductivity, lower noise floor, and more stable electromechanical response as compared to RGO‐based sensors. Abstract : Graphene nanosheets are synthesized by liquid phase exfoliation of graphite in water/ N ‐methylpyrrolidinone (NMP) solvents. The optimum ratio of water with NMP not only enhances the exfoliation yield and stability, but it also minimizes the defects in the graphene nanosheets. The as‐fabricated paper‐based strain sensors exhibit high electrical conductivity, low noise floor, and stable electromechanical response.